Analisis Kebangkrutan Pada Perusahaan Perbankan Di Indonesia Periode 2001-2012 (Dengan Menggunakan Model Altman Z-Score) - Aminah AMINAH; Andi Sanjaya (Jurnal Akuntansi dan Keuangan, 2013)
The purpose of this study is to provide empirical evidence about the bankruptcy prediction model used by Altman. Research questions were constructed in this study is whether the Altman Z-Score model that built in 1968 can be used and relied upon in accommodating economic climate in Indonesia, especially as a predictor of bankruptcy in Indonesia banking company. Statistical test results showed that the Altman Z-Score model appropriate for use in predicting the potential bankruptcy of the Indonesia banking company on the observation period 2001-2012. By doing so, this study conclude that the Altman Z-Score models can be a tool for predicting bankruptcy in Indonesia.